Identification of factors that stimulate the brown adipose tissue in healthy adults and patients - Lazaridi, A.V. (2020)
Obesity is caused by excess energy intake and/or low energy expenditure which contributes to the onset of many diseases including cardiovascular disease, diabetes and cancer. For this reason, many studies are focusing on the prevention of obesity as it is a crucial public health issue. In mammals, adipose tissue is comprised of white and brown adipose tissue (BAT). Their function differs, as the main role of the white adipose tissue is to store excess energy, whereas BAT can rapidly produce heat when stimulated, thereby, increasing the energy expenditure. Consequently, enhancing BAT activation could be a potential target to prevent and/or reduce obesity.